Faktor-Faktor Yang Mempengaruhi Kejadian Bayi Berat Lahir Rendah Pada Ibu Melahirkan di Ruang Perinatologi Rumah Sakit Umum Daerah 45 Kuningan - Widianingsih, Dian (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2012)
Introduction: One of the problems faced in the health field today is the Infant Low Birth Weight (LBW) increases risk of infant mortality, meaning that the infant mortality rate will increase when the incidence of low birth weight mounting. Target of in this study was to determine the effect of maternal characteristics on the incidence so that the incidence of LBW can be reduced. Method: this studies a descriptive correlation with cross-sectional picture of the relationship is to know the influence of variables that happen why LBW by maternal characteristics. Sample is total population are all them others who gave birth to LBW delivery in RSUD 45 in 2011 many as 92 people. The data collected is primary data, including hemoglobin level, nutritional status, maternal age, births pacing education, sosio-economic conditions, history of disease in the suffering mothers. Results: The results showed the characteristic of mothers who gave birth two babies with low birth weight is generally levels of HB > 11 gr% (57.3%), nutritional status of > 10 kg (54.3%), age 20-35 years (72.8%), low educational level (60,9%), the distance between the birth of < 2 years (54.3%), low sosio-economic conditions (71.7%), and a history of disease had no history of disease (54.3%). Bivariate analysis results in getting the effect of HB levels, nutritional status, distance between birth, sosio-economic conditions (r=0,439, r=0,383, r=0,422, r=0,206). There is no influence of age, education and history of the disease in the suffering mother (r=0.011, r= -0.042, r= -0,115). Age, education and history of the disease there was no effect on incidence of LBW because most people already know the result of the marriage at a young age and average education was fineshed junior high. Required optimalization of the implementation of education and promotion by nursing staff such as the addition of a health care facility to support treatment forlow birth weight infants in hospitals in RSUD 45 Kuningan.